Discussion of Consequences and Institutional Determinants of Unregulated Corporate Financial Statements: Evidence from Embedded Value Reporting - HAIL, LUZI (Journal of Accounting Research, 2011)
Serafeim [2011] examines the determinants and economic consequences of embedded value (EV) reporting, a voluntary disclosure arrangement in the life insurance industry. He finds substantial reductions in bid-ask spreads for EV reporting firms, and links the occurrence of this disclosure practice to the nature of competition in the insurance business. In my discussion, I focus on two aspects of his hypothesis development: (1) does EV reporting give rise to a credible commitment to transparency? (2) What are the country-level determinants of EV reporting? First, on a conceptual level, I highlight the distinction between an ex ante commitment to transparency and ex post voluntary disclosure. To illustrate my point, I examine the change in information asymmetry around various voluntary disclosure choices with varying degrees of commitment. I find a reduction in bidask spreads following U.S. cross-listings and the voluntary adoption of IFRS, but not after a switch to a Big Five auditor. These results let me gauge the magnitude of the effects for EV reporting. Second, I discuss the notion of complementarities among the elements of a country’s institutional environment. I then empirically show that institutional forces likely act both ways, i.e., from a single industry to the rest of the economy and vice versa, and that EV reporting is not independent from other voluntary commitment devices in a country. In sum, my findings underscore the importance of (and difficulties in) cleanly identifying the determinants and effects of voluntary disclosure choices. JEL classification: G14, G15, G30, K22, M41, M42